Development of Teaching Materials in the Shape of Encyclopedias in Social Studies Subjects for Pre-literate Materials - Athiyatul Hamidiyah; Anindya Fajarini (Institut Agama Islam Negeri Jember, 2022)
This research aims to (1) develop teaching material in the form of an encyclopedia in social studies subject for pre-literacy in VII grade at MTs Mambaul Huda Ngraseh in the 2020/2021 academic year, (2) to know the effectiveness of teaching material in the form of encyclopedia in social studies subject for pre-literacy in VII grade at MTs Mambaul Huda Ngraseh in the 2020/2021 academic year. This research is development research that uses Sugiyono’s development model as a line of research stages. Data analysis was used in this research, namely qualitative and quantitative data analysis techniques. The product that has been made, then validated by material experts, design experts, and linguists in sequence show: (1) the value of 77% is in the “valid” category, and the value of 92% is in the “very valid” category; (2) the value of 53% is in the “less valid” category, and the value of 92% is in the “very valid” category; (3) the value of 89% is in the “very valid” category. The trial result of small groups and large groups in the sequence indicates: (1) the value of 87,86% is in the “very effective” category; (2) the value of 87,20% is in the “very effective” category. The results of the questionnaire student's response get a score of 89% is in the “very interest” category. Based on the research, it can be concluded that teaching material in the form of an encyclopedia in social studies that experts have validated is worth using as a learning resource for social studies, and social studies teaching material in the form of an encyclopedia are effectively used as social science teaching materials for social studies subject for pre-literacy in VII Grade.